Firm migration patterns in in the Netherlands and in the United Kingdom. An end of twenty calm years of geographical interest - Ilaria Mariotti (European Regional Science Association (ERSA), 2001)
Firm migration in the Netherlands and the United Kingdom Cees-Jan Pen and Ilaria Mariotti In the 1970s firm migration was an important research topic in West European economic geography. Especially in the United Kingdom, but also in the Netherlands, Germany and France many migration studies are published. This paper describes a selection of these studies and proves the importance of this topic. These studies focused on assisting the in that time popular regional economic policy to support peripheral or old industrial areas by stimulating firms to move to these areas. It appeared that these policies were not very effective and the policy interest shifted to assist firms, which are located in these problem regions. Furthermore, especially in the United Kingdom the liberal policy of the Thatcher government aims at declining the governmental influence on for example firms. In a theoretical sense these policy oriented so-called behavioural firm migration studies are regarded as a repetition of (check)lists of push, pull and keep factors and interesting comments from time to time. This meant that the research interest focused on new theoretical approaches, which dealt with other themes. Since that time economic geographers regard behavioural firm migration research as a peripheral research theme, which results in hardly any theoretical contribution. So in a policy and in a scientific sense, it appears that since the 1980s the migration of firms is an insignificant topic. This implies that few studies are published and the insignificance also meant that no overview exists of the current state of the art. In a more theoretical sense, one of the authors found during the writing of his thesis international examples of a revival of the behavioural location theory and the connected firm migration research. We found signals, besides some examples of the classic interest in regional economic policy, that most of these migration studies focused on the suburbanisation of firms or in a more broad sense the urban spill-over. At the moment, this urban spill-over is an important policy topic, which pleas for data to ground this phenomenon and possibly also the significance of more long distance migration. We selected the Netherlands and the United Kingdom because these two countries produced most migration studies in Europe. Based on data of the English CREDO-database, we describe the importance and pattern of the migration of head offices in the period 1988-2000 for the United Kingdom. For the Netherlands we could only use firm migration data from 1986 until 1995. These figures are published by Kemper and Pellenbarg and are based on the so-called Mutation balance of the Chambers of Commerce. The paper mainly focuses on the comparison of firm migration process between the two countries in two different years: the 1995 for the Netherlands and the 1999 for the UK. The main results can be briefly described below. In the Netherlands 7,9% of all firms registered by the Chambers of Commerce have moved in 1995. The migration process involved 180,000 jobs. On the other hand, in the United Kingdom 3% of the business population have moved in 1999 and the amount of jobs involved was about 2,164,027. In addition, the business services are the most mobile sectors in both the countries, followed by the wholesale in the Netherlands and by the financial sector in the UK. Finally, the greater part of the firm migrations are short distance movements.
Keywords: 330